Calcium Dynamics in Basal Dendrites of Layer 5A and 5B Pyramidal Neurons Is Tuned to the Cell-Type Specific Physiological Action Potential Discharge - Krieger, Patrik; de Kock, Christiaan P. J.; Frick, Andreas (Frontiers in Cellular Neuroscience, 2017)
Layer 5 (L5) is a major neocortical output layer containing L5A slender-tufted and L5B thick-tufted pyramidal neurons. These neuron types differ in their in vivo firing patterns, connectivity, and dendritic morphology amongst other features, reflecting their specific functional role within the neocortical circuits. Here, we asked whether the active properties of the basal dendrites that receive the great majority of synaptic inputs within L5 differ between these two pyramidal neuron classes. To quantify their active properties, we measured the efficacy with which action potential (AP) firing patterns backpropagate along the basal dendrites by measuring the accompanying calcium transients using two-photon laser scanning microscopy in rat somatosensory cortex slices. For these measurements we used both “artificial” three-AP patterns and more complex physiological AP patterns that were previously recorded in anaesthetized rats in L5A slender-tufted (L5A-st) and L5B thick-tufted (L5B-tt) neurons in response to whisker stimulation. We show that AP patterns with relatively few APs (3APs) evoke a calcium response in L5B-tt, but not L5A-st, that is dependent on the temporal pattern of the three APs. With more complex in vivo recorded AP patterns the average calcium response was similar in the proximal dendrites but with a decay along dendrites (measured up to 100 µm) of L5B-tt but not L5A-st neurons. Interestingly however, the whisker evoked AP patterns – although very different for the two cell types – evoke similar calcium responses. In conclusion, although the effectiveness with which different AP patterns evoke calcium transients vary between L5A-st and L5B-tt cell, the calcium influx appears to be tuned such that whisker-evoked calcium transients are within the same dynamic range for both cell types.